Harnessing the potential of probiotics in the treatment of alcoholic liver disorders - Mishra, Garima; Singh, Pradeep; Molla, Mulugeta; Yimer, Yohannes Shumet; Dinda, Subas Chandra; Chandra, Phool; Singh, Bhuvnesh Kumar; Dagnew, Samuel Berihun; Assefa, Abraham Nigussie; Ewunetie, Amien (Frontiers in Pharmacology, 2023)
In the current scenario, prolonged consumption of alcohol across the globe is upsurging an appreciable number of patients with the risk of alcohol liver diseases. According to the recent report, the gut-liver axis is crucial in the progression of alcohol-induced liver diseases, including steatosis, steatohepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma. Despite several factors associated with alcoholic liver diseases, the complexity of the gut microflora and its great interaction with the liver have become a fascinating area for researchers due to the high exposure of the liver to free radicals, bacterial endotoxins, lipopolysaccharides, inflammatory markers etc. Undoubtedly, alcohol-induced gut microbiota imbalance stimulates dysbiosis, disrupts the intestinal barrier function, and trigger immune as well as inflammatory responses which further aggravate hepatic injury. Since currently available drugs to mitigate liver disorders have significant side effects, hence, probiotics have been widely researched to alleviate alcoholic liver diseases and to improve liver health. A broad range of probiotic bacteria like Lactobacillus, Bifidobacteria, E. coli, Sacchromyces, and Lactococcus are used to reduce or halt the progression of alcoholic liver diseases. Several underlying mechanisms, including alteration of the gut microbiome, modulation of intestinal barrier function and immune response, reduction in the level of endotoxins, and bacterial translocation, have been implicated through which probiotics can effectively suppress the occurrence of alcohol-induced liver disorders. This review addresses the therapeutic applications of probiotics in the treatment of alcoholic liver diseases. Novel insights into the mechanisms by which probiotics prevent alcoholic liver diseases have also been elaborated.